Effective Treatment of Rheumatoid Arthritis-Associated Interstitial Lung Disease by B-Cell Targeted Therapy with Rituximab - Wolfgang Hartung; Judith Maier; Michael Pfeifer; Martin Fleck (Case Reports in Immunology)
Rheumatoid arthritis- (RA-) associated interstitial lung disease (RA-ILD) is the extra-articular complication with most adverse impact on the quality of life and survival in RA patients. However, treatment options are limited and controlled studies are lacking. Here, we present the case of a 66-year-old patient suffering from severe RA-ILD, which has been successfully treated with Rituximab (RTX). After failure of conventional DMARD therapy, our patient showed sustained improvement of clinical pulmonary parameters as well as joint inflammation following B-cell depletion with RTX. The six-minute-walk test improved from 380 meters to 536 meters and the forced vital capacity from 2.49 liters to 3.49. The disease activity score could be reduced from 7.7 to 2.8. Therefore, RTX might be considered as an alternative treatment for RA-ILD in patients not responding to conventional DMARD therapy.